Rediscovering the Walisongo, Indonesia: A potential new destination for international pilgrimage - Fournié, Pierre (The international journal of religious tourism and pilgrimage, 2019)
The current paper explores the tradition of Walisongo, the nine saints or nine friends of God, that according to tradition initiated the islamisation of Java in the XV and XVI centuries. Largely unknown outside of Indonesia, the Wali Songo pilgrimage remains unfamiliar in the archipelago as well. Besides allowing a deeper understanding of the roots of Indonesian religious history and of the spread and acceptance of Islam, rediscovering the Wali Songo may help to reintroduce a peaceful image of the Muslim world. In such a way, reactivating the tradition of Wali Songo outside of the country but also inside, may support the idea of a peaceful religion of traders, of scholars and culture lovers open and able to integrate the traditions of other cultural groups. The Wali Songo are said to be at the origin of pesantren (Muslim religious schools) and largely used local arts and culture in their teachings. In an area of Central and East Java where minority groups may tend to impose the views of a reformist not to say a rigorist Islam, the Wali Songo teachings may offer a new common vehicle', a synonym of understanding, peace and cultural respect. If the development of international pilgrimage activity would suppose the setting up of proper infrastructures, to do so, may also boost new areas of services that would definitely support regional developments in the largest archipelago of the world and in a country that, besides being laic and governed by the principles of Pancasila, is before all the country worldwide with the largest number of Muslim citizens. In a planet currently governed by globalization, the origins of the Wali Songo, which are still relevant, if discussed, would demonstrate that ideas and religions can be shared, peacefully, across the land and seas.